Medical migration: A qualitative exploration of the atypical path of Japanese international medical graduates. (2nd January 2018) - Heist, Brian S.; Torok, Haruka Matsubara
Abstract: Background: International Medical Graduates (IMGs) are commonly understood to move from low to high resource countries with motivations including improved financial situations and cultures of emigration. A presumable exception to the above themes would be the Japanese IMG population. The aim of this study was to develop an understanding of the Japanese IMG experience. Methods: Using a grounded theory approach, we interviewed 19 Japanese IMGs working in the US and 16 Japanese IMGs working in Japan who had completed US clinical training. Questions addressed decision-making to pursue US clinical training, goals for the training, and career decision-making upon completing the training. Data collection and constant comparative analysis were conducted iteratively to identify emerging themes. Results: The emerging model of the Japanese IMG experience is focused around pivotal experiences that often include dissatisfaction with the quality of Japanese clinical training and personal exposures to US clinical education. Further decision-making in the pursuit of US residency is influenced by educator training quality, and clinical training and career opportunities. The desire to improve Japanese clinical training commonly influences career decision-making after US training. Conclusions: The Japanese IMG experience contrasts numerous perceptions of international physician migration and, in turn, enhances understanding of this paradigm.